2010
DOI: 10.1143/jpsj.79.083002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Chirality Selected by Mutual Antagonism

Abstract: To explore the mechanism of chiral symmetry breaking in a process of crystal growth under grinding, we propose a simple irreversible growth model of a lattice-gas with four possible states on a site: occupied by an achiral molecule A, or by a chiral enantiomer R or S, or empty. After two A molecules on neighboring sites form a chiral dimer R 2 or S 2 , clusters grow by incorporating A's at cluster periphery, irreversibly. Only the grinding recycles products R or S back to A. It is then demonstrated in kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…But, due to the complexity of the model, for instance, with dissolution and Ostwald ripening processes, identification of the essential mechanism seems to be elusive. Quite recently, we have further simplified the lattice-gas model such that achiral molecules A crystallize into R or S enantiomeric crystals irreversibly [19]. In the course of fitting simulation results of this ARS model, we have confirmed that the proximity of clusters with opposite enantiomers leads to the mutual antagonism, similar to the process proposed by Frank [9].…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…But, due to the complexity of the model, for instance, with dissolution and Ostwald ripening processes, identification of the essential mechanism seems to be elusive. Quite recently, we have further simplified the lattice-gas model such that achiral molecules A crystallize into R or S enantiomeric crystals irreversibly [19]. In the course of fitting simulation results of this ARS model, we have confirmed that the proximity of clusters with opposite enantiomers leads to the mutual antagonism, similar to the process proposed by Frank [9].…”
Section: Introductionsupporting
confidence: 70%
“…Due to the enhancement factor a ¼ 10, grown crystals are compact in a square-like shape, compared with the ramified clusters at a ¼ 1 shown in Ref. [19].…”
Section: ð2þmentioning
confidence: 88%
See 3 more Smart Citations